Implementasi Pendidikan Kewirausahaan dalam Kemandirian Santri di Pondok Pesantren - Fresyam Antika Ajeng; Rachmat Panca Putera (Departement of Mathematics Education, 2024)
This research is attemped to analyze the implementation of entrepreneurship education in Pondok Pesantren Minhajuth Thullab Way Jepara East Lampung. The research objectives are to find the implementation of entrepreneurship education and relevance with needs of the society. The research method applied in this study is quallitative. Data were collected such as observation, interview, and documentation. These data analyzed by triangulation method. The researcher used data reduction, display data, and verification to analyze the data. There are some research findings can be taken: 1) Implementation of entrepreneurship education based on Islam in Pondok Pesantren Minhajuth Thullab Way Jepara East Lampung is not optimal, this is due to lack of teachers qualified in the field of entrepreneurship, structure and infrastructure, and also limited capital owned businesses, 2) The mentor of Pondok Pesantren Minhajuth Thullab (Kiyai) has an important role , namely as the originator , pioneer , movers , and the direct supervisor of the program. The findings showed that the implementation of entrepreneurship education in Pondok Pesantren Minhajuth Thullab Way Jepara East Lampung still cannot be separated from the challenges and obstacles that must be faced.